Phenotype and cell proliferation activity of duct-like structures in human sublingual glands: a histological and immunohistochemical study - Elen de Souza TOLENTINO; Cleverson Soares TEIXEIRA; Luciana Reis AZEVEDO-ALANIS; Heitor Marques HONÓRIO; José Humberto DAMANTE (University of São Paulo, 2015)
There are several age-related microscopic changes in the salivary glands, including the increase in the number of duct-like structures (DLS). However, the true origin and the phenotype of the DLS are not known. Objective To evaluate the phenotype and the cell proliferation index of the DLS of human sublingual glands. Material and Methods Sixty sublingual glands obtained from human cadavers were divided into two groups - 0-30 and 61-90 years old. The phenotype was estimated by immunostaining for cytokeratin 19 (CK 19) and the S-100 protein as well as by the presence of mucin and glycogen. The cell proliferation index was determined by the Ki-67 antibody. The histochemical techniques used periodic acid-Schiff (PAS) and Alcian Blue. In each captured microscopic field, the DLS were counted to establish a percentage for the staining profile. The statistical analysis was accomplished using Student's t-test, the Mann-Whitney test and Pearson's correlation coefficient (p<0.05). Results Comparing both groups, only CK 19 showed a statistically significant difference (p=0.033), with the strongest expression in the elderly group. There was no significant difference between PAS and Alcian Blue (p=0.270). In both groups, the immunostaining for CK 19 was stronger than that for S-100 (p=0.004;p<0.001), but there was no correlation between the two immunomarkers (ρ=-0.163; p=0.315). There was no immunostaining for Ki-67. Conclusions DLS demonstrate a ductal phenotypic profile and do not present cell proliferation activity. DLS may represent a regressive process arising from acini or represent the result of metaplasia.